LANGKAH –LANGKAH PENERAPAN SHARED READING METHOD UNTUK PENGAJARAN MEMBACA PERMULAAN DI KELAS II SEKOLAH DASAR - Ma'ruf, Leila Maulida; Salim, Herli (Universitas Pendidikan Indonesia Kampus Serang, 2022)
Reading is a process carried out and utilized by readers to obtain messages that the writer wants to convey through written language. Reading is one of the four aspects of language skills which is the main door to entry into knowledge. In this study, the process of beginning reading for second grade elementary school students will be explained. The approach taken in this research was qualitative using the Shared Reading method. The qualitative approach was specifically chosen by the researcher to consider the data sources that will be processed and the research methods that will be used through analysis of a document in the form of a learning video. In this research, content analysis was chosen as the method used, where the researcher carried out several stages in processing the data, including selecting the data, then separating and organising the data to be used, then explaining it by describing the data, until making a conclusion at the end. The results of research in video analysis show that there are three stages of learning in reading together, namely exploration, discovery and independence. The following are detailed data findings based on analysis of three learning videos using the Shared Reading method: The first video contains 9 learning steps with 1 exploration activity, 3 discovery activities and 5 independent activities, the second video contains 8 learning steps with 1 exploration activity, 4 discovery activities , and 3 independent activities, then the third video contains 4 learning steps with 2 exploration activities, 1 discovery activity, and an independent activity. Thus, researchers can conclude that beginning reading in class II elementary school students can use the method of reading together through Big Book media.